STRATEGI OPTIMALISASI ELECTORAL CREDIBILITY OLEH ELECTION STAKEHOLDERS DALAM MEMAKSIMALKAN VOTER TURNOUT DAN CEGAH VOTE BUYING PADA PILKADA NEW NORMAL 2020 - Evsa Wulan Suri; Yuneva Yuneva (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2020)
This study examines the Electoral Credibility Optimization Strategy by Election Stakeholders in Maximizing Voter Turnout and preventing Vote Buying in the 2020 New Normal Election. Substantive quality of electoral democracy. Massive socialization, education, and literacy efforts are needed by election stakeholders so that the quality of procedural and substantial democracy is maintained without creating opportunities for the pandemic epicenter and new clusters for the spread of Covid 19. The main factors affecting participatory and substantive quality in the era new normal is how the form of political socialization carried out by election stakeholders to form the voters' electoral mindset in the new normal period. This research uses descriptive methods. qualitative. The technique of collecting data is through primary data obtained from in-depth interviews with election organizer stakeholders. Secondary data collection by citing books, journals, documents, and online media. Data analysis techniques through data reduction activities, data display, and drawing conclusions. The result of the research is that election organizer stakeholders have made efforts and strategies in optimizing Electoral Credibility in Maximizing Voters-Turnout and preventing Vote Buying in the 2020 New Normal Pilkada through a series of socialization, education and literacy.